Truthmakers (are indexed combinations) - Wolfgang Freitag (Studia Philosophica Estonica, 2008)
My aim is to show that theories which try to construct truthmakers out of objects and properties/relations alone are not tenable: The Frege–Wittgenstein idea of incompleteness does not yield truthmakers. Armstrong’s theory of partial identity and the theory of moments, i.e., of non-transferable properties, yield truthmakers, but these theories have counter-intuitive consequences. I conclude that the notion of a truthmaker makes ontological demands beyond objects and properties/relations and propose that truthmakers are exemplification relations which are necessarily tied to objects and properties/relations.